Could SO2 and CO2 emissions trading schemes achieve co-benefits of emissions reduction?. (November 2022) - Hu, Yucai; Li, Ranran; Du, Lei; Ren, Shenggang; Chevallier, Julien
Abstract: The challenge of air pollution and climate change has resulted in the emergence internationally of emission trading systems (ETSs) related mainly to SO2 emissions and CO2 emissions. Although the effectiveness of ETSs has been discussed extensively, it remains unclear whether such policies aimed at reducing different types of emissions are able to achieve overall emissions reductions. Based on China's pilots of SO2 ETS and CO2 ETS, we employ a DID model and investigate the synergistic effects of SO2 ETS and CO2 ETS. The results show first, that the SO2 ETS and CO2 ETS reduced SO2 and CO2 emissions, indicating effective implementation of these policies, second, that the synergistic emissions reduction effect suggests that the SO2 ETS has a limited effect on reducing CO2 emissions due to the maturity of SO₂ capture technologies but that the CO2 ETS significantly reduced SO2 emissions and achieved the co-benefits of SO2 emission reduction, third, further analysis showed that the co-benefits of CO2 ETS derive from reduced fossil energy consumption and improved energy efficiency whereas the impact of the SO2 ETS is limited. This work adds to empirical evidences on the synergistic effects of ETS, which is conductive to optimize the policy design to achieve synergistic emissions reduction effect. Highlights: We find China's SO2 ETS and CO2 ETS effectively reduced SO2 and CO2 emissions. The SO2 ETS has a limited synergistic emissions reduction effect on reducing CO2 emissions. The CO2 ETS significantly reduced SO2 emissions and achieved the co-benefits of SO2 emission reduction. The co-benefits of CO2 ETS derive from reduced fossil energy consumption and improved energy efficiency.